2007
DOI: 10.1093/aob/mcm121
|View full text |Cite
|
Sign up to set email alerts
|

Progress in Research and Development on Hybrid Rice: A Super-domesticate in China

Abstract: BackgroundChina has been successful in breeding hybrid rice strains, but is now facing challenges to develop new hybrids with high-yielding potential, better grain quality, and tolerance to biotic and abiotic stresses. This paper reviews the most significant advances in hybrid rice breeding in China, and presents a recent study on fine-mapping quantitative trait loci (QTLs) for yield traits.ScopeBy exploiting new types of male sterility, hybrid rice production in China has become more diversified. The use of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
335
2
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(346 citation statements)
references
References 20 publications
(21 reference statements)
1
335
2
8
Order By: Relevance
“…The CMS-WA system, which is most widely used for hybrid rice production since 1970s, was developed by successive backcrossing to introduce the CMS cytoplasm of a male sterile O. rufipogon plant into the nuclear backgrounds of rice cultivars [8,9]. We previously identified the CMS-WA gene WA352 (here renamed WA352c, see below) and revealed that WA352c causes CMS by interaction with the nucleus-encoded, highly conserved mitochondrial protein COX11, leading to premature programmed cell death in the anther tapetum and defective pollen development.…”
Section: Introductionmentioning
confidence: 99%
“…The CMS-WA system, which is most widely used for hybrid rice production since 1970s, was developed by successive backcrossing to introduce the CMS cytoplasm of a male sterile O. rufipogon plant into the nuclear backgrounds of rice cultivars [8,9]. We previously identified the CMS-WA gene WA352 (here renamed WA352c, see below) and revealed that WA352c causes CMS by interaction with the nucleus-encoded, highly conserved mitochondrial protein COX11, leading to premature programmed cell death in the anther tapetum and defective pollen development.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic improvement (GI) in rice plays a crucial role in the yield increase in China and even in the world (Cheng et al, 2007;Zhang et al, 2007). As an integral part of plant organs, plant roots are involved in acquisition of water and nutrients, synthesis of plant hormones, organic acids and amino acids, and anchorage of plants (Fitter et al, 2002;Inukai et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Rice is strictly selfpollinating; therefore, hybrid varieties are bred using male-sterile maternal lines that fail to produce viable pollen, thus preventing self-pollination. Hybrid rice breeding uses the well-developed three-line and two-line systems 4,5 . The three-line system uses a cytoplasmic male-sterile (CMS) line, a restorer line and a CMS maintainer line to produce F 1 hybrid seeds and maintain the CMS line [6][7][8] .…”
mentioning
confidence: 99%
“…The three-line system uses a cytoplasmic male-sterile (CMS) line, a restorer line and a CMS maintainer line to produce F 1 hybrid seeds and maintain the CMS line [6][7][8] . Three-line hybrid rice has been grown since the 1970s and is a major type of hybrid rice 1,4,9 . However, the limited germplasm resources of restorer lines and the genetic diversity between CMS and restorer lines have limited further improvements in three-line breeding 10 .…”
mentioning
confidence: 99%